Catcalling dan Kesehatan Mental Berhubungan dengan Kepercayaan Diri Mahasiswi - Rahma, Irsya Maiza; Fayyaza, Saniya; Ingtyas, Fatma Tresno; Ginting, Laurena (Fakultas Ilmu Kesehatan, 2025)
Catcalling or verbal harassment in public spaces is a phenomenon often experienced by women, including female students, which can have a negative impact on their mental health and self-confidence. This study aims to analyze the relationship between catcalling experiences, mental health, and self-confidence in female students of Universitas Negeri Medan (UNIMED). This study used a quantitative approach with a correlational design. The sample consisted of 30 female students selected using a purposive sampling technique. Data were collected through a Likert scale-based questionnaire and analyzed using validity, reliability, normality, Pearson correlation tests, and multiple linear regression. The results showed that catcalling had a significant effect on self-confidence with a Pearson correlation value of 0.687 (p <0.05), which indicated a negative impact, especially on women. In addition, mental health was also shown to significantly affect self-confidence (r count = 0.493, p <0.05), where individuals with good mental health tend to have higher self-confidence. Repeated catcalling significantly decreases mental health, which ultimately has a negative impact on self-confidence. These findings underscore the importance of preventive and intervention efforts to protect female students from catcalling and raise public awareness of its impact. This study provides recommendations for campuses to create a safe environment and support female students' mental well-being and self-confidence.